Metody ustalania poziomu retencji w wybranych typach umów reasekuracyjnych - Poprawska, Ewa; Kowalczyk, Patrycja (Methods of Setting Optimal Reinsurance Retentions in Selected Types of Reinsurance Contracts, 2008)
A main parameter that must be fund during making a decision about reinsurance contract is a decision which part of risk must be transferred to reinsurer and which may stay in insurance company -the level optimal reinsurance retention. This level depends on: solvency requirements, financial capacity of insurer, level of loss, volatility in loss levels, type of reinsurance contract. The aim of the paper is to present methods of setting optimal reinsurance retentions in selected types of reinsurance contracts and to analyze the influence of reinsurance contracts on main factors of finance in insurance companies of different profiles of risk accepted.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 377-385